Translation as Metaphor, the Translator as Anthropologist - Osimo, Bruno (Vertimo studijos, 2019)
The presence/absence of the notion of “inner language” in different cultures creates a watershed between various cultures as far as the notion of “translation” is concerned. Intersemiosity is seen, accordingly, as inner or outer process to interlingual translation. This gap is reflected in the metaphors attached to translation. By analysing them, the author gets a picture of the cultural roots of the view of translation in each culture. Anthropology can be a precious ally in the reciprocal definition of “translation” and “culture”. A new trope for translation is suggested: metaphor.
Keywords: anthropologist; intersemiosity; metaphor; translation